ULTRASOUND AND SUPINE CHEST RADIOGRAPH IN ROAD TRAFFIC ACCIDENT PATIENTS: A RELIABLE AND CONVENIENT WAY TO DIAGNOSE PLEURAL EFFUSION - Mumtaz, Uzma; Zahur, Zainab; Raza, Muhammad Ali; Mumtaz, Madiha (Journal of Ayub Medical College Abbottabad, 2017)
Background: Portable bed side ultrasound and supine chest radiograph of 80 traumatic patients excluding very clinically unstable patients who subsequently underwent CT scan chest was done for traumatic effusion showing that ultrasound had a higher sensitivity than CXR, 88.23% and 77.94%, respectively, and a similar specificity of 100% and 100%, respectively. Objective of the study is to compare the diagnostic accuracy of high resolution ultrasound and supine chest x-ray in detection of pleural effusion in road traffic accident patients keeping plain CT chest as gold standard. Methods: This study was conducted in PIMS and PAEC General Hospital, Islamabad from 1st January to 15th December 2015. The current study examined total of 80 trauma (blunt and penetrating) patients coming to emergency departments of both hospitals specifically those who had road traffic accident history. Their portable bed side ultrasound and supine chest radiograph were performed for assessing pleural effusion and subsequently CT scan chest was done for confirmation as it's a gold standard. Results: Using CT findings as gold standard the sensitivity, specificity, positive predictive value and negative predictive value was assessed for both ultrasonography and chest radiography and found to be 88.23%,100%, 100%, 40% and 77.94%, 100%, 100%, 55.55% respectively with diagnostic accuracy of ultrasound 90% as compared to 81.25% for supine chest x-rays when compared with gold standard. Conclusion: Ultrasound and chest x-ray can be used as a useful and suitable adjunct to CT in road traffic accident patients as these are easily available, non-invasive, no contrast required, can be performed on bed side and carries no or little radiation risk. Keywords: Ultrasound; Chest x-ray; Computed tomography; Road traffic accident; Trauma